Saints and Celibates : Protestant Identity in the Irish Novels of William Trevor - Dineen, Gerard (Trinity College (Dublin, Ireland). School of English, 1999)
This thesis focuses purely on Protestant identity in three Irish novels by William Trevor, namely: Fools of Fortune, The Silence in the Garden and Reading Turgenev.
Keywords: Anglo-Irish Literature, M.Phil.; M.Phil. Trinity College Dublin, 1999